Polyembryony in "Dent Composite" maize - Silva, Jairo; Magnavaca, Ricardo; Freire, Adelson de Barros (Pesquisa Agropecuaria Brasileira, 2014)
The frequency of polyembryony in "Dent Composite" maize was studied during three generations of controlled progeny self-pollination. Following established norms for seed testing, the seeds were placed in germinators. Seeds with multiple coleoptiles and primary roots were transplanted to Mitscherlich pots in the greenhouse and later to field plots. The increase of the multiple seedling frequency from S0 to S2, greater than 500 times, indicates the hereditability of the character. Correlation between polyembryony and prolificness and with oil and balanced protein content are suggested as new areas of research of interest for corn breeding.